2019
DOI: 10.1515/pp-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic intraperitoneal chemotherapy with cisplatin and mitomycin C for colorectal cancer peritoneal metastases: A systematic review of the literature

Abstract: BackgroundThe randomized trial PRODIGE 7 failed to show the benefit of oxaliplatin hyperthermic intraperitoneal chemotherapy (HIPEC) in colorectal peritoneal metastasis treatment (CR PM). This systematic review focuses on the association of cisplatin (CDDP) with mitomycin C (MMC) in HIPEC in CR PM.ContentExperimental studies demonstrated that hyperthermia, in addition to CDDP ± MMC treatment, gradually improved the cytotoxic effect by increasing early apoptosis, eATP interaction, intracellular CDDP concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
(107 reference statements)
0
14
0
2
Order By: Relevance
“…A detailed discussion on this approach is outside the scope of this review. Interested readers may like to further explore through some recent reviews on this approach (184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194).…”
Section: Hyperthermia: a Chemosensitizermentioning
confidence: 99%
“…A detailed discussion on this approach is outside the scope of this review. Interested readers may like to further explore through some recent reviews on this approach (184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194).…”
Section: Hyperthermia: a Chemosensitizermentioning
confidence: 99%
“…Regarding PRODIGE 7 trial, subgroup analysis showed a significant survival benefit for CRS + oxaliplatin HIPEC vs CRS for a subgroup with PCI 10-15[ 15 ]. Thus, there is a need of further studies, stratifying patients by PCI and prospectively examining the relative therapeutic effectiveness of MMC and oxaliplatin.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of cisplatin and MMC is also frequently used and seems to be a valid HIPEC protocol in peritoneal metastases of CR origin. Recent studies evaluating this protocol demonstrated prolonged survival with limited toxicity[ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermic intraperitoneal chemotherapy (HIPEC) with cisplatin and mitomycin C (Figure 10c) (obtained from Streptomyces caespitosus) is the only protocol to demonstrate an adjuvant HIPEC benefit in colorectal cancer patients at high risk for peritoneal failure and an alternative to highdose and short-term oxaliplatin [566]. 5-FU plus mitomycin remains the preferred chemotherapy in most patients with anal cancer [567]. Bleomycin (Figure 10e) is an antibiotic complex of several glycopeptides derived from Streptomyces verticillus, gained FDA approval in July 1973.…”
Section: Mundulea Sericeamentioning
confidence: 99%